Ultra-sensitive determination of Ochratoxin A in coffee and tea samples using a novel semi-automated in-syringe based coagulant-assisted fast mycotoxin extraction (FaMEx) technique coupled with UHPLC-MS/MS. (15th August 2023) - Prakasham, Karthikeyan; Gurrani, Swapnil; Shiea, Jentaie; Wu, Ming-Tsang; Wu, Chia-Fang; Lin, Yu-Chia; Tsai, Bongee; Huang, Po-Chin; Andaluri, Gangadhar; Ponnusamy, Vinoth Kumar
Graphical abstract: Highlights: A novel in-syringe-based coagulant-assisted microextraction technique was developed. Ferrous sulfate as a coagulation agent exhibited excellent matrix elimination. This method utilizes semi-automated setups with minimal sample and solvent amounts. This protocol is a simple, highly-sensitive, low-matrix effect and efficient procedure. Applied for the analysis of mycotoxin in coffee and tea samples using LC-MS/MS. Abstract: In this study, we demonstrated a novel semi-automated in-syringe-based coagulant-assisted liquid–liquid microextraction (IS-CGA-LLME) as fast mycotoxin extraction (FaMEx) technique coupled with ultra-high-performance liquid chromatography connected with a tandem-mass spectrometer (UHPLC-MS/MS) for the quantification of mycotoxin (Ochratoxin A, OT-A) in coffee and tea samples. IS-CGA-LLME is a three-step extraction process that includes extraction of OT-A from sample matrix using low-volume solvent extraction, then the extractant was cleaned-up using a coagulation process, and finally, the decolorized/matrix removed sample solution was processed for LLME for target analyte's pre-concentration. The final extractant was analyzed using UHPLC-MS/MS for OT-A quantification. Under the optimized experimental conditions, highly sensitive detection and quantification limits were obtained at 0.001 and 0.003 ng g −1 for OT-A with excellent extraction recovery (93–111%) and precision <10%. These results proved that the developed method is a simple, highly sensitive, semi-automated, low-matrix effect and efficient procedure for the determination of mycotoxins in food samples.